Facies characterisation of a shallow-water deltaic succession: the Upper Jurassic Wagad Sandstone Formation of Kachchh, western India - Joseph, Jaquilin K.; Patel, Satish J. (Geologos, 2018)
Ancient deltaic facies are difficult to differentiate from tidally influenced shallow-marine facies. The Wagad Sandstone Formation of the Wagad Highland (eastern Kachchh Basin) is typified by offshore and deltaic facies with sedimentary characteristics that represent different conditions of hydrodynamics and related depositional processes. The study area, the Adhoi Anticline, constitutes a ~154-m-thick, shale-dominated sequence with progressive upward intercalations of bioturbated micritic sandstone and quartz arenite. Two thick Astarte beds (sandy allochemic limestone), with an erosional base and gravel blanketing, illustrate tidal amplification and high-energy stochastic events such as storms. Sedimentological characteristics document three depositional facies: an offshore, shale-dominated sequence prograding to proximal prodeltaic micritic sandstone and quartz arenite with sandy allochemic limestones, further prograding to mouth bars and abandoned channel deposits. The Wagad Sandstone Formation displays depositional environmental conditions that are dissimilar from those of coeval deposits in Kachchh sub-basins as well as on regional and global scales. This is attributed to a reactivation of the Kachchh Mainland and South Wagad faults which resulted in detachment and uplift of the Wagad block which then experienced prograding deltaic conditions.